THE INFLUENCE OF ELECTRONIC WORD-OF-MOUTH ON GOFOOD PURCHASE DECISION THROUGH BRAND IMAGE AND BRAND TRUST IN SOLO RAYA - Akbar Eko Marjiyanto; Septi Kurnia Prastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the mechanism of the influence of Electronic Word-of-Mouth (E-WOM) on GoFood service Purchase Decisions, by testing the dual mediating role of Brand Image and Brand Trust. Motivated by the inconsistency of previous research findings and the phenomenon of declining GoFood GMV amidst intense competition, this study uses a quantitative causal associative approach. Primary data were collected through an online questionnaire from 154 GoFood users in Solo Raya, an area with a relevant young digital population, using a purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a bootstrapping procedure of 5,000 samples. The main results reject the hypothesis of a direct influence of E-WOM on Purchase Decisions (H5). Conversely, E-WOM is proven to have a positive and significant influence on Brand Image (H2) and Brand Trust (H1). These two mediator variables are then proven to be positive and significant drivers of Purchase Decisions (H3 and H4 are supported). The central finding of this study is the confirmation of full mediation, where Brand Image (H7) and Brand Trust (H6) fully mediate the relationship between E-WOM and Purchase Decision. This finding strongly supports the Stimulus-Organism-Response (S-O-R) theoretical framework; E-WOM (Stimulus) does not directly trigger a Response (Purchase), but must first be processed to build cognitive and affective assets (Organism).